Demographic Characteristics, Need For Achievement And Entrepreneurial Attitude Among Women Entrepreneurs And Women Managers In Malaysia - Lim, Chee Chee (1995)
The present study investigated the demographic characteristics need for achievement and entrepreneurial attitude among women entrepreneurs and women managers in Malaysia. Specifically, it aimed to provide answers to the following research questions: (1) Will women entrepreneurs differ from women managers demographic characteristics, need for achievement and entrepreneurial attitude? (2) Will the demographic characteristics significantly explain the variance in need for achievement and entrepreneurial attitude? (3) What demographic characteristics will best predict need for achievement and entrepreneurial attitude among women entrepreneurs and women managers under study?To answer the research questions, a descriptie quantitative study was conducted. The units of analysis women entrepreneurs and women managers in Malaysia. Forty five (45) women entrepreneurs and 45 women managers were included in the study through snowballing or "referred participants" due to the absence of a systematic listing of women entrepreneurs and women managers. Questionnaires were distributed to target respondents either personally or by mail. The response rate was 31.3%. The instrument used consisted of three parts: the Demographic Survey to gather personal information, the Rosen Scale and the Entrepreneurial Attitude Scale developed by Nieves (198.5) to measure need for achievement and entrepreneurial attitude among women entrepreneurs and women managers respectively. The last two yielded reliability coefficiently of 0.89 and 0.85 respectively. data were analyzed using the T-test to test differences; Multiple Regression Analysis to determine the relationships between demographic characteristics, on the one hand, and for achievement and entrepreneurial attitude on the other hand; and Stepwise Regression Analysis (Best Fit Model) to determine the demographic characteristics that best predict need for achievement and entrepreneurial attitude. The 0.05 level of significance was used as critical level for decision-making regarding the hypotheses. The major findings of the study are as follows: (1) Women entrepreneurs did not differ significantly form women managers in demographic characteristics (except for age, marital status, level of education and family size), need for achievement and entrepreneurial attitude. (2) The thirteen demographic characteristics did not significantly explain the variance in need for achievement and entrepreneurial attitude. Demographic characteristics explained only 15.00% in the variance for need for achievement and only 13.82% in the variance for entrepreneurial attitude. (3) The best fit model showed that the demographic characteristics which are good predictors of need for achievement are: (i) age, (ii) aggregate annual family income (iii) family size (iv) relationship with the father (v) realtionship with the mother, and (vi) frequency of rewards received from parents. Meanwhile, the entrepreneurial attitude, the good predictors are (i) family size, (ii)level of education of the father, (iii) relationship with the mother, and (iv) place of residence during childhood. (4)The best predictor for need for achievement is socio-economic status measured by aggregate annual family income while the best predictor for entrepreneurial attitude is level of education of the father. Based on the findings, recommendations for further studies, policies formulation and programs/ trainings towards entrepreneurship development are forwarded.